Decolonizing Native Histories Collaboration, Knowledge, and Language in the Americas - Mallon, Florencia E. (Duke University Press, 2011)
Decolonizing Native Histories is an interdisciplinary collection that grapples with the racial and ethnic politics of knowledge production and indigenous activism in the Americas. It analyzes the relationship of language to power and empowerment, and advocates for collaborations between community members, scholars, and activists that prioritize the rights of Native peoples to decide how their knowledge is used. The contributors-academics and activists, indigenous and nonindigenous, from disciplines including history, anthropology, linguistics, and political science-explore the challenges of decolonization.These wide-ranging case studies consider how language, the law, and the archive have historically served as instruments of colonialism and how they can be creatively transformed in constructing autonomy. The collection highlights points of commonality and solidarity across geographical, cultural, and linguistic boundaries and also reflects deep distinctions between North and South. Decolonizing Native Histories looks at Native histories and narratives in an internationally comparative context, with the hope that international collaboration and understanding of local histories will foster new possibilities for indigenous mobilization and an increasingly decolonized future.